Transformation of youth national identity in the context of globalization - Shikirtayev, B.B.; Yessengaliyeva, V.A. (NLC «Karaganda National Research University named after acad. Ye.A. Buketov», 2025)
The article examines the features of the transformation of young people’s national identity in the context of globalization processes. It analyzes the contradictions between the desire to preserve national uniqueness and the influence of global culture, digital technologies, and mass communication. The authors demonstrate that globalization does not destroy national identity but rather stimulates its rethinking, contributing to the formation of hybrid forms of self-consciousness that combine elements of local and global culture. The aim of the study is to provide a comprehensive analysis of the transformation of youth identity in worldview, cultural, and social contexts. Special attention is paid to the structure of national self-consciousness, the issues of harmonizing national consciousness and cultural identity under globalization, as well as innovative approaches and cultural practices that influence the formation of the personal and social image of young people. The paper also addresses the ethical, social, and aesthetic aspects of the formation of youth identity
Social philosophy - Әлеуметтік философия - Социальная философия
Keywords: youth; national identity; globalization; culture; digitalization; transformation; sociocultural processes